Structure of the crust and the lithosphere in the Himalaya-Tibet region and implications on the rheology and eclogitization of the India plate - Hetényi, György; Vergne, Jérôme; Nábĕlek, John L; Cattin, Rodolphe; Brunet, Fabrice; Bollinger, Laurent; Diament, Michel (Himalayan Journal of Sciences, 2008)
<!--[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--> <!--[if gte mso 10]> <![endif]--> DOI = 10.3126/hjs.v5i7.1267 Himalayan Journal of Sciences Vol.5(7) (Special Issue) 2008 p.65-66